Interdisciplinary Analysis of the Lehi Horse: Implications for Early Historic Horse Cultures of the North American West. Issue 3 (July 2021) - Taylor, William Timothy Treal; Hart, Isaac; Jones, Emily Lena; Brenner-Coltrain, Joan; Thompson Jobe, Jessica; Britt, Brooks B.; McDonald, H. Gregory; Li, Yue; Zhang, Chengrui; Le Roux, Petrus; Shield Chief Gover, Carlton Quinn; Schiavinato, Stéphanie; et al.
Abstract : Although recognized as one of the most significant cultural transformations in North America, the reintroduction of the horse to the continent after AD 1492 has been rarely addressed by archaeological science. A key contributing factor behind this limited study is the apparent absence of equine skeletal remains from early historic archaeological contexts. Here, we present a multidisciplinary analysis of a horse skeleton recovered in Lehi, Utah, originally attributed to the Pleistocene. Reanalysis of stratigraphic context and radiocarbon dating indicates a historic age for this horse (cal AD 1681–1939), linking it with Ute or other Indigenous groups, whereas osteological features demonstrate its use for mounted horseback riding—perhaps with a nonframe saddle. DNA analysis indicates that the animal was a female domestic horse, which was likely cared for as part of a breeding herd despite outliving its usefulness in transport. Finally, sequentially sampled stable carbon, oxygen, and strontium isotope values from tooth enamel (δ 13 C, δ 18 O, and 87 Sr/ 86 Sr) suggest that the horse was raised locally. These results show the utility of archaeological science as applied to horse remains in understanding Indigenous horse pastoralism, whereas consideration of the broader archaeological record suggests a pattern of misidentification of horse bones from early historic contexts.